A Study of Sino-Indian Business Negotiations-from a Cross-cultural Perspective - Yu-xian, Zhang (Journal of Asian Business Strategy, 2013)
With the continuous development of economy, the economic cooperation worldwide is becoming more and more frequent than before. China and its neighboring country India communicate and interact more frequently than ever with each other, which lead to the increase of the international business negotiation and the increase of the international business conflicts subsequently. Among the factors attributing to the conflicts, cross-culture is one major element, which also becomes increasingly important. This thesis discusses the cross-culture in business negotiation between china and India from various aspects, especially in business etiquettes to open a good situation and promote the successful proceeding of business negotiation and further trade communication between China and India.